(untitled) (مجلة الواحات للبحوث والدراسات, 2021)
Heritage Is The Repository Of The Nation’s Thought, Its Culture And Literature, As Well As The Link Between Its Generations. Recently, Heritage Has Emerged As A Problematic Issue In Various Fields, In Various Fields Of Knowledge, And The Issue Of Discussion Is Being Deliberated In Many Ways, Including The Artistic Aspect Of How To Use The Heritage In Its Artistic Appearance, As An Effective Tool In The Debate Of Modern Ideas And Modern Topics, And It Becomes More Important, Accurate And Sensitive When It Comes To The Use Of Heritage In The Literature Of The Child Because It Is A Complex Educational And Technical Process. Keywords Heritage , Child Literature , Algeria , Myths , Berber